PRACTICE OF ATTRACTING GRANTS, FUNDS AND INTERNATIONAL FINANCIAL RESOURCES IN HIGHER EDUCATION (Global Conference on Medical and Health Sciences, 2026)
Higher education institutions today operate in a complex and competitive global environment, where securing sufficient financial resources is crucial for sustaining academic excellence, research, and innovation. Traditional funding sources, such as government allocations and tuition fees, are often insufficient to cover the increasing costs of infrastructure, faculty development, scientific research, and student services. Consequently, the practice of attracting grants, funds, and international financial resources has become an essential strategy for universities aiming to ensure financial stability and enhance their global competitiveness.